Graphene Oxide: A Novel 2‐Dimensional Material in Membrane Separation for Water Purification. Issue 5 (31st January 2017) - Fathizadeh, Mahdi; Xu, Weiwei L.; Zhou, Fanglei; Yoon, Yeomin; Yu, Miao
Abstract : As a newly emerging 2‐dimensional (2‐D) material with sub‐nanometer thickness, graphene oxide (GO) has been widely studied either as a pure/skeleton membrane material or as an additive in and a functional coating on matrix membranes for water purification because of its unique physico‐chemico‐mechanical properties. Manipulating or incorporating this novel 2‐D material effectively into a membrane structure has been shown to significantly improve membrane performance, including increased water permeability, alleviated fouling, improved antibacterial properties, etc., which will eventually lead to lower energy consumption, longer lifetime, and lower maintenance cost. As the pure/skeleton membrane material, GO flakes typically are deposited as a lamellar structure by solution‐based coating processes on appropriate porous supports, and nano‐channels between GO sheets and sometimes structural defects within GO could be utilized as transport passage. As an effective additive and surface functional coating, GO also shows great potential to improve water permeation, surface hydrophilicity, and chemical resistance. In this paper, the latest studies on the use of GO in membrane application for water purification are reviewed, and potential challenges are discussed. Moreover, possible future research directions to further develop GO or GO‐incorporated membranes for water purification are suggested in different membrane separation processes. Abstract : Manipulating or effectively incorporating graphene oxide (GO), a novel 2‐dimensional material, into a membrane structure in three different forms, including i) pure/skeleton membrane material, ii) additive in and iii) functional coating on matrix membranes, is shown to significantly improve water purification performance.